Development of an algorithm for the management of cervical lymphadenopathy in children: consensus of the Italian Society of Preventive and Social Pediatrics, jointly with the Italian Society of Pediatric Infectious Diseases and the Italian Society of Pediatric Otorhinolaryngology. Issue 12 (2nd December 2015) - Chiappini, Elena; Camaioni, Angelo; Benazzo, Marco; Biondi, Andrea; Bottero, Sergio; De Masi, Salvatore; Di Mauro, Giuseppe; Doria, Mattia; Esposito, Susanna; Felisati, Giovanni; Felisati, Dino; Festini, Filippo; et al.
Abstract : Cervical lymphadenopathy is a common disorder in children due to a wide spectrum of disorders. On the basis of a complete history and physical examination, paediatricians have to select, among the vast majority of children with a benign self-limiting condition, those at risk for other, more complex, diseases requiring laboratory tests, imaging and, finally, tissue sampling. At the same time, they should avoid expensive and invasive examinations when unnecessary. The Italian Society of Preventive and Social Pediatrics, jointly with the Italian Society of Pediatric Infectious Diseases, the Italian Society of Pediatric Otorhinolaryngology, and other Scientific Societies, issued a National Consensus document, based on the most recent literature findings, including an algorithm for the management of cervical lymphadenopathy in children.Methods : The Consensus Conference method was used, following the Italian National Plan Guidelines. Relevant publications in English were identified through a systematic review of MEDLINE and the Cochrane Database of Systematic Reviews from their inception through March 21, 2014.Results : Basing on literature results, an algorithm was developed, including several possible clinical scenarios. Situations requiring a watchful waiting strategy, those requiring an empiric antibiotic therapy, and those necessitating a prompt diagnostic workup, considering the risk for a severe underling disease, have been identified.Conclusion : The present algorithm is a practice tool for the management of pediatric cervical lymphadenopathy in the hospital and the ambulatory settings. A multidisciplinary approach is paramount. Further studies are required for its validation in the clinical field.